2017
DOI: 10.3343/alm.2017.37.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Association ofFoxp3Polymorphism With Allograft Outcome in Kidney Transplantation

Abstract: BackgroundForkhead box P3 (Foxp3) is the most reliable marker for regulatory T cells, which play an important role in maintaining renal allograft tolerance. Recently, Foxp3 polymorphisms have been reported to be associated with graft outcome in kidney transplantation. We analyzed the association of Foxp3 polymorphisms with renal allograft outcome.MethodsFoxp3 polymorphisms (rs3761548 A/C, rs2280883 C/T, rs5902434 del/ATT, and rs2232365 A/G) were tested by PCR with sequence-specific primers (PCR-SSP) in 231 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The mutations in FOXP3 and Treg cell deficiency result in the development of various autoimmune diseases in humans as is well described in the Immunodysregulation Polyendocrinopathy Enteropathy X‐linked (IPEX) syndrome . Moreover, some FOXP3 gene polymorphisms could affect the function and quantity of the FOXP3 protein and thus influence the Treg function, being associated with various inflammatory and autoimmune diseases . Several polymorphisms were reported in the promoter, intron, and exon regions of the FOXP3 gene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations in FOXP3 and Treg cell deficiency result in the development of various autoimmune diseases in humans as is well described in the Immunodysregulation Polyendocrinopathy Enteropathy X‐linked (IPEX) syndrome . Moreover, some FOXP3 gene polymorphisms could affect the function and quantity of the FOXP3 protein and thus influence the Treg function, being associated with various inflammatory and autoimmune diseases . Several polymorphisms were reported in the promoter, intron, and exon regions of the FOXP3 gene .…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, some FOXP3 gene polymorphisms could affect the function and quantity of the FOXP3 protein and thus influence the Treg function, being associated with various inflammatory and autoimmune diseases. 28 Several polymorphisms were reported in the promoter, intron, and exon regions of the FOXP3 gene. 29 The promoter is involved in initiation of transcription and therefore is among the major elements that control gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, heterogeneous results have been documented for both SNPs. [30][31][32][33][34] In conclusion, we could not identify any association between SNPs rs4794067, rs2275806, and rs2232365 mapping in the genes of TBX21, GATA3, and FOXP3 and acute cellular liver transplant rejection. In contrast, the SNP rs3761548 (−3279C>A) of the FOXP3 gene displays an association with l-BPACR.…”
mentioning
confidence: 55%
“…The other studies investigated the selected FOXP3 SNPs for association with acute rejection and graft survival in the context of kidney transplantation. Finally, heterogeneous results have been documented for both SNPs …”
Section: Demographic and Clinical Characteristics Of Liver Transplantmentioning
confidence: 99%
“…FOXP3 c.-22-902A>G and c.-23+2882A>C polymorphisms were not related to long term acute rejection in kidney recipients, even when the analysis was carried out considering male as hemizygous and grouping with correspondent homozygous genotypes (data not shown). A previous study also did not find association of both FOXP3 variant with acute or chronic rejection, even in a 10-years follow-up period ( Park et al, 2017 ). On the other hand, other studies reported association of the FOXP3 c.-23+2882A>C (A allele) polymorphism with long-term (2 and 5 years) acute rejection or nephrotoxicity in kidney recipients from different populations treated with cyclosporine- or TAC- based immunosuppressive therapy ( Qiu et al, 2012 ; Misra et al, 2016 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 76%